Teacher Discourse for Third Grade Language Arts and Mathematics Classes in the Chilean School System: A Case Study - Perez Sobarzo, Fernanda (2021)
Understanding student and teacher interactions is an essential part of the teaching-learning process, given that quality of these interactions in the classroom define pedagogical processes (Mourshed, Chijioke and Barber, 2012). A third-grade teacher discourse when teaching Mathematics and Language Arts was analyzed with regards to length and intent as well as the types of questions posed to identify cognitive skills elicited among students. The obtained data was transcribed and analyzed from audio recordings. Based on the results, teacher discourse dominated classroom time and questions which were predominantly close-ended, content-focused and more focused on the promotion of low-order cognitive skills. It was concluded that this aspect must be purposefully addressed by teachers. We, therefore, recommend that teachers gain insight early on in their training about designing strategies to promote higher-order cognitive learning in the classroom.